Polymer Composite Based No-Core Fiber Structure as Refractive Index Sensor - Nur Najahatul Huda Saris; Nazirah Mohd Razali; Toshimi Fukui; Takaaki Ishigure; Marinah Othman; Azura Hamzah; Nurul Ashikin Daud (Trans Tech Publications, Ltd., 2025)
Index by ERA (Tier 2)